ANALISIS AMANAT DALAM PUISI MENJADI IBU KARYA OKA RUSMINI - maya mardiana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This paper contains the mandate in Oka Rusmini's poem Menjadi Ibu . This study was chosen because the researcher considers that mandate plays an important role in a poetry work, so that readers get the message that the writer wants to convey to the reader to be applied in everyday life. This study aims to determine the message / mandate contained in Oka Rusmini's poem Menjadi Ibu. The method used is a qualitative description, namely describing the results of the study in words using the object to be studied by paraphrasing word for word so that it knows the meaning the writer wants to convey in the poem. The result of the analysis of one of the elements in the poetry is mandate. The mandate contained in the poem menjadi ibu by Oka Rusmini is that the roles of a mother and father must be balanced in forming a family so that no one feels disadvantaged.